2018
DOI: 10.1097/wnp.0000000000000441
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Periodic Discharges With and Without Triphasic Morphology

Abstract: Triphasic morphology GPDs confer less risk of seizures when compared with patients with GPDs without triphasic morphology. Features with a higher risk of seizures include focality on electroencephalogram, interburst suppression, a history of epilepsy, and an abnormal scan. The GPD score can be used to assess the risk of developing seizures in patients with GPDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 13 publications
1
12
0
1
Order By: Relevance
“…This was similar to a study examining the IRA for EEGs of comatose patients in general [21], as well as a study specifically examining GPDs that found that among 20 patients, the IRA for 'triphasic morphology' was only fair (κ of 0.33) [22]. In a retrospective cohort study of 92 patients with GPDs, the IRA for 'triphasic morphology' was "substantial," with a κ of 0.67 [23]. However, this study utilized only two raters, where the prior IRA study for GPDs used 11 to rate EEGs; this difference could have contributed to the disparity in the IRA.…”
Section: Updated Terminology and Interrater Agreementsupporting
confidence: 80%
See 1 more Smart Citation
“…This was similar to a study examining the IRA for EEGs of comatose patients in general [21], as well as a study specifically examining GPDs that found that among 20 patients, the IRA for 'triphasic morphology' was only fair (κ of 0.33) [22]. In a retrospective cohort study of 92 patients with GPDs, the IRA for 'triphasic morphology' was "substantial," with a κ of 0.67 [23]. However, this study utilized only two raters, where the prior IRA study for GPDs used 11 to rate EEGs; this difference could have contributed to the disparity in the IRA.…”
Section: Updated Terminology and Interrater Agreementsupporting
confidence: 80%
“…Variables with a statistically significant risk of having seizures included focality on EEG, interburst suppression, history of epilepsy, an abnormal neuroimaging test, and generalized pattern without triphasic morphology. GP-D+TW had a statistically significant decreased risk of seizures [23]. However, others have noted that their definition of GP-D+TW does not appear in line with ACNS guidelines and this may have influenced their findings [30].…”
Section: Nonconvulsive Status Epilepticus and Seizuresmentioning
confidence: 93%
“…We added 13 other articles. [60][61][62][63][64][65][66][67][68][69][70][71][72] Therefore, we analyzed a total of 21 investigations. 31,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] Bibliographic characteristics and description of the EEG features reported in this studies can be found in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Triphasic waves may assume an ictal pattern and be associated with seizures. This is particularly true in high-risk patients with a focality on EEG, inter-burst suppression, a history of epilepsy, and abnormal neuroimaging findings (72). Various authors have suggested an algorithm to distinguish ictal appearing TW pattern to facilitate correct therapeutic intervention and avoid unnecessary use of ASMs (69).…”
Section: Generalized Periodic Patterns With Triphasic Morphologymentioning
confidence: 99%